محاكاة عملية الاحتراق في محركات الديزل ذات الحقن المباشر, باستخدام النماذج شبه البعدية - غدير, نبيل; علي, عارف; زيود, أزد (Latakia University Journal -Engineering Sciences Series, 2019)
تلبية لمتطلبات تخفيض زمن وكلفة تطوير المحركات, فإن أدوات المحاكاة تستخدم للتصميم الأمثل الأولي لدورة العمل الترموديناميكية. وبسبب تزايد درجات الحرية في أنظمة إدارة المحركات, فإن التركيز موجه على أدوات المحاكاة ذات زمن الحساب القصير. وتصف هذه المقالة طريقة مبتكرة لتطوير نماذج الاحتراق شبه البعدية, بالاستخدام المتعدد لتوابع ﭬيبي Viebe's functions. وتتضمن نماذج لتأخر الاشتعال, مرحلة الاشتعال السريع, مرحلة الاشتعال البطيء, مرحلة الاشتعال المتأخر. والتي طورت لتصف مجالاً واسعاً من حالات عمل محركات الديزل ذات الحقن المباشر. In order to save time and cost for engine development, simulation tools are used for pre-optimization of the thermodynamic working cycle. Due to the increasing number of possible degrees of freedom in engine management system, the focus is on simulation tools with short computation time. This paper describes a generic strategy for the development of Quasi-dimensional combustion models using multi-Viebe's function. Models for ignition delay, pre-mixed combustion phase, mixing-controlled combustion phase, and late combustion phase were developed based on equations describing a wide range of working cases involving direct injection diesel engines.